The Effect of the Overlapping Teaching Style (Prince and Training) On the Performance of Some Free Skills in Rhythmic Gymnastics for Female Students Aged (13-14) Years in Baghdad Governorate - Nadeem Ahmed, Maysaa (International Journal of Psychosocial Rehabilitation, 2020)
The overlap in the teaching methods used in a single educational unit through a set of teaching methods and access to the application of a coherent educational method (leadership and training), which is one of the renewed cases in teaching some free skills in rhythmic gymnastics, through the synthesis and overlap between two diverse styles of effective teaching methods In learning, which aims at discipline, control, and accuracy, as well as increasing the number of iterative attempts and the student’s participation in giving educational behavioral decisions in the contents of education. In line with some free skills in rhythmic housing for students from 13–14 years old in Baghdad governorate, the importance of the research lies in being an experimental attempt by the researcher to introduce a new teaching method through merging and overlapping. Two methods of teaching with one teaching style, which is the overlap of teaching methods (prince and training). The research aims to - Learn about the effect of using the multidisciplinary teaching method (prince and training) on improving the performance of some free skills in rhythmic gymnastics for female students (13–14) years old in Baghdad governorate. - As for imposing research, it is - There are statistically significant differences in the teaching method for interoperability (orientation and training) in free skills in the rhythmic and pre-posterior body tests in favor of the post-test. The sample represented 24 female students of the second intermediate grade in Baghdad governorate, and the research included the application of four free skills in rhythmic gymnastics. After completing the application of the teaching method (leadership and training), the data were processed statistically, and the results were interpreted and discussed, and the results were reached. The following conclusions 1. The emergence of statistically significant differences between the results of the pretest and the posttest in a sliding step with a jump step (step by step) in favor of the posttest. 2. The emergence of statistically significant differences between the results of the pre and post tests in (jumping and marital upbringing) in favor of the post test. 3. The emergence of statistically significant differences between the results of the two pre- and post-tests in the three-step front (front waltz) and in favor of the post-test. 4. The emergence of statistically significant differences between the results of the pre- and post-test on the front scale and in favor of the post-test. As for the recommendations, they were 1. The use of an interlocking teaching method (leadership and training) in teaching and learning other skills in rhythmic gymnastics that has not been addressed in the current study for female students (13-14) years old. 2. Teacher counter by holding training courses to clarify the importance of using the teaching method for interoperability (orientation and training) in teaching and learning activities and individual and group game skills in the physical education lesson instead of the traditional method of teaching. 3. Conducting a similar study for the same proposed teaching method to develop the mental, physical, and motor capabilities that were addressed in the current study and for students of both sexes.